2011
DOI: 10.4028/www.scientific.net/amr.239-242.1190
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Biomimetic Superhydrophobic CuO Surface Prepared by a Facile and Inexpensive Environmental-Friendly Method

Abstract: A facile and inexpensive environmental-friendly method was developed to prepare a biomimetic superhydrophobic CuO surface with hierarchical micro- and nanostructures by the combination of a simple solid state reaction and a convenient dipping-coating method. The biomimetic CuO surface showed superhydrophobicity even for some corrosive liquids including salt solutions and acidic and basic solutions at a wide pH range from 2 to 13. Moreover, the superhydrophobic CuO surface showed high stability in ambient envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We found that the static CA (162 ± 2 • ) of CuO nanowires grown on porous copper at 550 • C for 24 h is higher than that (152 ± 1.8 • ) of CuO nanowires synthesized on normal copper foil at 550 • C for 24 h. This enhancement of wettability performance may due to the higher surface roughness and more dense and long CuO nanowires growth on porous copper substrates, which can trap a larger fraction of air within the grooves. The advancing and receding CAs of the CuO nanowire sample synthesized at 550 • C for 24 h are also studied using the method reported by Yuan et al [51]. Remarkably, the advancing and receding CAs are determined to be 163 ± 2.4 • and 160 ± 2.6 • , respectively (see supporting information figure S1 available at stacks.iop.org/Nano/24/ 065602/mmedia).…”
Section: Water Contact Angle Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that the static CA (162 ± 2 • ) of CuO nanowires grown on porous copper at 550 • C for 24 h is higher than that (152 ± 1.8 • ) of CuO nanowires synthesized on normal copper foil at 550 • C for 24 h. This enhancement of wettability performance may due to the higher surface roughness and more dense and long CuO nanowires growth on porous copper substrates, which can trap a larger fraction of air within the grooves. The advancing and receding CAs of the CuO nanowire sample synthesized at 550 • C for 24 h are also studied using the method reported by Yuan et al [51]. Remarkably, the advancing and receding CAs are determined to be 163 ± 2.4 • and 160 ± 2.6 • , respectively (see supporting information figure S1 available at stacks.iop.org/Nano/24/ 065602/mmedia).…”
Section: Water Contact Angle Measurementsmentioning
confidence: 96%
“…Tremendous efforts have been devoted to exploring the synthesis of nanostructures based on copper substrates for applications in superhydrophobic surfaces, including etching [42], electrodeposition [43], an electroless plating combined isothermal oxidizing technique [44], solution immersion [45][46][47][48][49], and surface oxidation [50]. As a result, nanoscale CuO with different morphologies, such as CuO microcabbages [45], CuO hierarchical nanostructures [50], CuO nanorods and microflowers [47], CuO/Cu(OH) 2 nanoneedle arrays [49], flower-like CuO and Cu(OH) 2 nanorods [46], nanosized CuO thin film [44] and other CuO nanostructures [48,51,52] synthesized on copper surfaces have been extensively reported. Nevertheless, although some of these reported methods [45][46][47][48][49][50] are simple and possess the potential for practical applications, most of them [42][43][44][45][46]50] generally require special apparatus or tedious fabrication processes along with certain chemical reagents.…”
Section: Introductionmentioning
confidence: 99%